Stopping slash-and-burn - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An NGO in Zambia has volunteers living with forest communities, in order to build up trust and work together on alternatives to slash-and-burn agriculture.